Przekład jako transfer międzykulturowy a role tłumacza - Agnieszka Kruk (Ksiegarnia Akademicka Publishing, 2018)
Translation as an Intercultural Transfer – the Translator’s Roles In the process of translation, especially in intercultural translation, the translator exercises different functions. Some of them are permanent, while others change depending on the type of text, recipients’ expectations or predominant strategies. The purpose of this paper is to separate, divide and describe the roles played by the translator in the process of translating texts which contain elements of foreign cultures. The awareness of the complexity of the functions exercised by the translator and of the consequences of their decisions should help translators in choosing the most advantageous translation strategies which will allow them to show the readers all the cultural richness of the original.